Oropharyngeal examination as a predictor of obstructive sleep apnea: pilot study of gag reflex and palatal reflex - Juliana Spelta Valbuza; Márcio Moysés de Oliveira; Cristiane Fiquene Conti; Lucila Bizari F. Prado; Luciane B.C. Carvalho; Gilmar Fernandes do Prado (Arquivos de Neuro-Psiquiatria)
Obstructive sleep apnea (OSA) has high prevalence and may cause serious comorbities. The aim of this trial was to show if simple noninvasive methods such as gag reflex and palatal reflex are prospective multivariate assessments of predictor variables for OSA. METHOD: We evaluate gag reflex and palatal reflex, of fifty-five adult patients, and their subsequent overnight polysomnography. RESULTS: Forty-one participants presented obstructive sleep apnea. The most relevant findings in our study were: [1] absence of gag reflex on patients with severe obstructive apnea (p=0.001); [2] absence of palatal reflex on moderate obstructive apnea patients (p=0.02). CONCLUSION: Gag reflex and palatal reflex, a simple noninvasive test regularly performed in a systematic neurological examination can disclose the impact of the local neurogenic injury associated to snoring and/or obstructive sleep apnea syndrome.